Analysis of Factors Affecting Healthy Reproductive Behavior in Adolescents in the Digital Era - Zumrotul Ula; Rasi Rahagia; Suprapto (The Indonesian Institute of Science and Technology Research, 2025)
Adolescents in the digital era face opportunities and challenges in maintaining healthy reproductive behavior due to easy access to information and social media influence. This quantitative cross-sectional study surveyed 320 high school students aged 15–19 in Surabaya, Indonesia, using stratified random sampling. Data collected from April–July 2025 via self-administered questionnaires were analyzed with descriptive statistics, chi-square tests, correlations, and logistic regression. The findings showed that 62.5% of adolescents had good reproductive behavior, which was significantly associated with high knowledge (73.3% vs. 36.8%, p < 0.001), positive attitudes (71.4% vs. 45.5%, p = 0.001), strong parental guidance (80.6% vs. 39.3%, p < 0.001), supportive peer influence (73.7% vs. 46.2%, p = 0.002), and controlled digital media exposure (80.0% vs. 41.4%, p < 0.001). Multivariate analysis identified strong parental guidance (AOR = 3.65; 95% CI: 2.12–6.28) and controlled digital media exposure (AOR = 3.21; 95% CI: 1.85–5.58) as the strongest predictors, followed by high knowledge (AOR = 2.45), positive attitudes (AOR = 1.78), and supportive peers (AOR = 1.92). In conclusion, adolescent reproductive behavior is shaped by a combination of individual, family, peer, and digital factors, with parental guidance and digital literacy emerging as the most critical protective elements. Strengthening family involvement and promoting responsible digital engagement are recommended to foster healthy adolescent reproductive behavior.